Effect of specific exercise strategy on need for surgery in patients with subacromial impingement syndrome: randomised controlled study. Issue 19 (11th September 2014) - Holmgren, Theresa; Hallgren, Hanna Björnsson; Öberg, Birgitta; Adolfsson, Lars; Johansson, Kajsa
Abstract : STUDY QUESTION: Can a specific exercise strategy improve shoulder function and pain in patients with subacromial impingement syndrome, thereby decreasing the need for arthroscopic subacromial decompression? SUMMARY ANSWER: Compared with a control exercise group, patients in the specific exercise group had significantly greater improvements in shoulder function and pain and fewer patients needed surgery at the three month assessment. WHAT IS KNOWN AND WHAT THIS PAPER ADDS: Different exercise programmes are used as first line treatment in patients with subacromial impingement syndrome, but conclusive evidence to support the efficacy for these programmes is lacking. This specific exercise strategy proved effective in improving shoulder function and pain in patients in whom earlier conservative treatment had failed.